Penerapan Komunikasi Pemasaran Terpadu untuk Meningkatkan Brand Awareness dan Penjualan UMKM Smoothies Fruits - Santi Rimadias; Dinda Nurfira Rindiani; Salfa Firyal Ninada; Sisilya Fujiya; Surya Migel Sinurat (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
This dedication to the community aims to design an effective integrated marketing strategy to enhance brand awareness and sales of Smoothies Fruits, a small business producing fresh smoothies without added sugar or preservatives. By employing an Integrated Marketing Communication (IMC) approach, this research analyzes market conditions, identifies target audiences, and develops appropriate communication strategies. The results of the social media campaign showed increased reach, impressions, and engagement, successfully attracting new customers. This study provides guidance for small businesses in formulating more focused and effective marketing strategies to improve competitiveness in an increasingly challenging market.